Pengembangan Modul Ajar Materi Perubahan Lingkungan Tema Sampah Plastik - Nurwendah, Anisa Solehah; Yayan Sanjaya; Mimin Nurjhani Kusumastuti (Jurnal Biotek, 2023)
The teaching module is one of the supporting factors for success in the learning process. A good teaching module must follow the demands of the curriculum and be based on the needs and real-life situations experienced by students. This research aims to develop a valid learning module with environmental change material on plastic waste. The method used in this research adapts the ADDIE method. The instruments used in this research were (1) a validation sheet given to biology lecturers, religion lecturers, and a lay outer, and (2) teacher and student response sheets. The validation sheet and the teacher and student questionnaires provided quantitative data that was collected. The parameter used to test the validity of the teaching module is Aiken's V. The result of Aiken's V score for the teaching module is 0.67 (valid), with the average score of student and teacher responses being 87 (very good). The conclusion of this study shows that the teaching module is valid, with righteous responses from teachers and students, indicating that this teaching module can support biology learning.